A vision for smart and sustainable cities. Issue 4 (2nd December 2021) - Elnashai, Amr; Mahmoud, Hussam
Abstract: Our built environment is characterized by large, ever‐expanding and highly complex cities. The spatial extent of the interconnected systems that serve these cities leads to higher vulnerability to disruption. On the other hand, climate change and political instability have noticeably increased the frequency of natural and human‐induced hazards. Recalling that risk is the product of vulnerability and hazard, it is evident that large cities are experiencing unprecedented levels of risk. While major investments and numerous research, development and implementation efforts have been dedicated to address natural and human‐induced risk to large cities, there is still a lack of system‐of‐systems level considerations and a comprehensive, interdependent vision for creating cities that respond effectively to severe disruptions. On this note, the authors envision the city of the future, its features and its operational modes. The requirements of creating such smart and sustainable, hence optimally resilient, cities dictate research‐to‐implementation consequences. A high‐level view of these requirements and their implications on research and development is provided.